Perbandingan Hasil Belajar Mahasiswa Bekerja Dengan Tidak Bekerja - Syahputri, Viny; Fitri, Dira Zahara; Damanik, Rizki Ramadhan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aim of this research is to find out whether there are differences in the learning outcomes of students who work and students who do not work. This study uses quantitative methods with comparative studies. The results of this research, which was carried out using an independent sample t-test, show that the learning outcomes of working students are different from those of students who do not work. More research is needed on how the learning outcomes of working and non-working students differ.